2016
DOI: 10.1007/s00234-016-1756-0
|View full text |Cite|
|
Sign up to set email alerts
|

Perfusion imaging of brain gliomas using arterial spin labeling: correlation with histopathological vascular density in MRI-guided biopsies

Abstract: ASL can be a useful noninvasive perfusion MR method for quantitative evaluation of the MVD of brain gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Volume of biopsy sample was 300-900 mm 3 . All 37 patients had gliomas confirmed by pathology, which consisted of 20 HGG patients with mean age 49 ± 11 years, and 17 LGG patients with mean age 43 ± 15 years (Table 1). Age difference between HGG and LGG patients was not significant (P = 0.165, two tails).…”
Section: Patient Groups and Tissue Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Volume of biopsy sample was 300-900 mm 3 . All 37 patients had gliomas confirmed by pathology, which consisted of 20 HGG patients with mean age 49 ± 11 years, and 17 LGG patients with mean age 43 ± 15 years (Table 1). Age difference between HGG and LGG patients was not significant (P = 0.165, two tails).…”
Section: Patient Groups and Tissue Samplesmentioning
confidence: 99%
“…Dynamic susceptibility contrast‐enhanced MR (DSC‐MR) perfusion has been employed to assess microvessel area . Recent studies have shown that ASL can also be used to measure microvascular density in glioma and nonfunctioning pituitary macroadenoma . In addition, relationships have been established between VEGF expression and parameters derived from contrast media‐dependent MR perfusion techniques, such as DSC‐MR and T 1 ‐weighted dynamic contrast‐enhanced MRI in glioma, meningioma, and rectal carcinoma .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several researches have shown that ASL can help discriminate high- and low-grade gliomas [7], [8]. Although some studies [9], [10], [11], [12] suggested that CBF obtained from ASL may have relationships with histopathologic parameters, such as vascular density and epidermal growth factor receptor status. Few studies focus on the correlations of perfusion with IDH1 genotype and 1p/19q status.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, arterial spin labeling is not affected by the blood–brain barrier, and truly reflects the degree of perfusion. Arterial spin labeling can be applied repeatedly in children and restless patients [30] and assesses cerebral blood flow, which represents blood flow in a specific organ per unit. Tumor angiogenesis usually occurs during tumor progression from low to high grade and is characterized by increased blood flow.…”
Section: Discussionmentioning
confidence: 99%